Abundance, activity and critical habitat of the striped dolphin Stenella coeruleoalba in the Gulf of Taranto (northern Ionian Sea, central Mediterranean Sea). Issue 2 (21st December 2017) - Carlucci, Roberto; Ricci, Pasquale; Cipriano, Giulia; Fanizza, Carmelo
Abstract: Abundance, density, daily variation in group size, activity and habitat use of the striped dolphin in the Gulf of Taranto (northern Ionian Sea, central Mediterranean Sea) were investigated using data from sightings collected between April 2009 and December 2016 during standardized vessel‐based surveys. Density and abundance were estimated in the survey area by means of conventional distance sampling, resulting in 0.97 specimens/km 2 (CV = 5.77%; 95% CI = 0.86–1.08 specimens/km 2 ) and 615 specimens (CV = 5.77%; 95% CI = 549–689 specimens), respectively. Group size data were analysed using multivariate methods. The changes in group size, depth and percentage occurrence of activity between daily periods were investigated with non‐parametric tests. The spatio‐temporal distribution of the striped dolphin in each predominant activity was investigated by means of the ordinary Kriging method. Fifteen year‐maps of spatial prediction were produced, allowing the identification of persistent areas. The results delineate a critical habitat of about 150 km 2 in the northernmost 'Taranto Valley' canyon system ranging between 140 and 910 m in depth. This critical habitat was persistently and regularly used by an important estimated population of striped dolphins for their day‐to‐day survival and maintenance in a healthy condition. The intense human use occurring in the area highlights the need for local, national and EU management to set a comprehensive strategy. The establishment of a SPAMI (Specially Protected Area of Mediterranean Importance) as an effective tool for the conservation of the species is suggested. The consequence of establishing a closed area could be reasonably accepted by local concurrent stakeholders. Indeed, limiting access through the establishment of this small closed area would result in the protection of a habitat acting as an ecological refuge for many other pelagic and demersal species of commercial interest, thus favouring their spill over.